2012
DOI: 10.1016/j.freeradbiomed.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte DNA replication in growing liver requires either glutathione or a single allele of txnrd1

Abstract: Ribonucleotide reductase (RNR) activity requires an electron donor, which in bacteria, yeast, and plants is usually either reduced thioredoxin (Trx) or reduced glutaredoxin (Grx). Mice lacking glutathione reductase are viable and, although mice lacking thioredoxin reductase 1 (TrxR1) are embryonic-lethal, several studies have shown that mouse cells lacking the txnrd1 gene, encoding TrxR1, can proliferate normally. To better understand the in vivo electron donor requirements for mammalian RNR, we here investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 53 publications
8
61
0
Order By: Relevance
“…7C. Also, recent in vivo data show that either glutathione or a single allele of the TrxR-dependent redox pathway can independently support hepatocyte DNA replication and proliferation (29).…”
Section: Thioredoxin Oxidation Results In Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…7C. Also, recent in vivo data show that either glutathione or a single allele of the TrxR-dependent redox pathway can independently support hepatocyte DNA replication and proliferation (29).…”
Section: Thioredoxin Oxidation Results In Cell Deathmentioning
confidence: 99%
“…Tan et al (28) found that the Trx system can function as an alternative system to reduce glutathione disulfide in Saccharomyces cerevisiae. It was also found that in mice, normal cell proliferation without TrxR1 occurred both embryonically and during liver regeneration (29).…”
mentioning
confidence: 96%
“…Importantly, our data indicate that TrxR1 inhibition is only detrimental in settings of GSH system disruption. Work by ourselves and others suggests that a cross-talk between the Trx and GSH systems most reasonably explains the tolerance of TrxR1 inhibition in vivo and in vitro (2,23,34,38,39,42). Other than dietary riboflavin deficiency that is easily correctable, GSH system deficiencies are virtually unknown in humans supporting the translational potential of ATG or other TrxR1 inhibitors for the treatment of lung injury in human patients (10)(11)(12).…”
Section: Figmentioning
confidence: 98%
“…Conrad and colleagues demonstrated that, although cells from TrxR1-deficient mice have normal proliferative capacity, they exhibit heightened sensitivity to the GSH synthesis inhibitor buthionine sulfoximine (BSO) (8). In addition, Schmidt and colleagues showed that hepatocyte DNA replication requires either GSH or TrxR1 (9). This finding was recently confirmed in primary human T lymphocytes (10), where the two systems are required for optimal activity of ribonucleotide reductase.…”
Section: The Trx and Gsh Systems: Redundancy And Crosstalkmentioning
confidence: 99%